Synergistic enhancement of antibacterial efficacy via graft conjugation of antibacterial peptides onto antibacterial polymers - Ozburun, Damla Gokkaya; Hancer, Hande; Ozbek, Tulin; Ozmen, Mehmet Murat; Topuzogullari, Murat (TAYLOR & FRANCIS INC, 2025)
This study presents the design, synthesis, and characterization of a novel graft conjugate integrating an antibacterial cationic quaternized copolymer, poly(4-vinylpyridine-co-N-(2-hydroxypropyl) methacrylamide) [P(4VP-co-HPMA)], with the antibacterial peptide CRWWRWWR. The copolymer was synthesized via free radical polymerization, sequentially quaternized to introduce permanent positive charges and carboxylic acid side groups, and subsequently conjugated to the peptide through amide bond formation. Structural and compositional analyses by GPC, 1H-NMR, and fluorescence spectroscopy confirmed successful conjugation, with an average of 1.97 peptide molecules per polymer chain. The graft conjugate exhibited minimum inhibitory concentrations (MICs) of 16 mu g/mL against Escherichia coli and 8 mu g/mL against Staphylococcus aureus, outperforming both the free peptide and copolymer against S. aureus. MTT assays on L929 fibroblast cells revealed that at MIC levels, cell viability remained above 70%, with cytotoxicity being dose-dependent. The enhanced antibacterial activity of the graft conjugate compared to individual components highlights the synergistic effect of molecular architecture, where polymer-peptide integration combines the structural stability of the polymer with the potent bioactivity of the peptide. These findings demonstrate that graft conjugation is an effective strategy for developing high-efficacy antibacterial materials with potential applications in biomedical and antibacterial surface technologies.
Keywords: Antibacterial; conjugate; graft; quaternization; peptide; polycation; ACTION MECHANISM; Polymer Science